Dual energy computed tomography angiography of a pulmonary embolized port catheter fragment - Henzler, Thomas; Diehl, Steffen J.; Jochum, Susanne; Süselbeck, Tim; Schönberg, Stefan; Fink, Christian (Journal of cardiovascular medicine, 2011)
We present the case of a 64-year-old woman with a history of breast cancer who underwent explantation of a dysfunctional intravenous port system. At surgery a broken port catheter was found. A port catheter fragment embolized into the segmental artery of the posterobasal segment of the right inferior lobe, causing a wedge-shaped segmental perfusion defect in the corresponding segment. The catheter was removed by catheter intervention with a goose-neck snare.
Gesehen am 06.10.2022